Self-reported concussion history: impact of providing a definition of concussion - Robbins CA; Daneshvar DH; Picano JD; Gavett BE; Baugh CM; Riley DO; Nowinski CJ; McKee AC; Cantu RC; Stern RA (Dove Medical Press, 2014)
Clifford A Robbins,1 Daniel H Daneshvar,1,2 John D Picano,1,3 Brandon E Gavett,1,4 Christine M Baugh,1,2 David O Riley,1 Christopher J Nowinski,1,2,5 Ann C McKee,1,2,6–8 Robert C Cantu,1,5,9,10 Robert A Stern1,2,8,91Center for the Study of Traumatic Encephalopathy, 2Department of Neurology, Boston University School of Medicine, Boston, MA, USA; 3School of Medicine and Biomedical Sciences, University of Buffalo, Buffalo, NY, USA; 4Department of Psychology, University of Colorado, Colorado Springs, CO, USA; 5Sports Legacy Institute, Waltham MA, USA; 6United States Department of Veterans Affairs, VA Boston Healthcare System, Boston, MA, USA; 7Department of Pathology, 8Alzheimer's Disease Center, 9Department of Neurosurgery, Boston University School of Medicine, Boston, MA, USA; 10Department of Neurosurgery, Emerson Hospital, Concord, MA, USABackground: In recent years, the understanding of concussion has evolved in the research and medical communities to include more subtle and transient symptoms. The accepted definition of concussion in these communities has reflected this change. However, it is unclear whether this shift is also reflected in the understanding of the athletic community.What is known about the subject: Self-reported concussion history is an inaccurate assessment of someone's lifetime exposure to concussive brain trauma. However, unfortunately, in many cases it is the only available tool.Hypothesis/purpose: We hypothesize that athletes' self-reported concussion histories will be significantly greater after reading them the current definition of concussion, relative to the reporting when no definition was provided. An increase from baseline to post-definition response will suggest that athletes are unaware of the currently accepted medical definition.Study design: Cross-sectional study of 472 current and former athletes.Methods: Investigators conducted structured telephone interviews with current and former athletes between January 2010 and January 2013, asking participants to report how many concussions they had received in their lives. Interviewers then read participants a current definition of concussion, and asked them to re-estimate based on that definition.Results: The two estimates were significantly different (Wilcoxon signed rank test: z=15.636, P<0.001). Comparison of the baseline and post-definition medians (7 and 15, respectively) indicated that the post-definition estimate was approximately twice the baseline. Follow-up analyses indicated that this effect was consistent across all levels of competition examined and across type of sport (contact versus non-contact).Conclusion: Our results indicate that athletes' current understandings of concussions are not consistent with a currently accepted medical definition. We strongly recommend that clinicians and researchers preface requests for self-reported concussion history with a definition. In addition, it is extremely important that researchers report the definition they used in published manuscripts of their work.What this study adds to existing knowledge: Our study shows that unprompted reporting of concussion history produces results that are significantly different from those provided after a definition has been given, suggesting one possible mechanism to improve the reliability of self-reported concussion history across multiple individuals.Keywords: concussion, self-report, sports-related concussion